Investments and capital stocks as estimations for health infrastructure in the European countries (EU28) - Michael Koch (Europäisches Institut für Sozioökonomie e. V., 2018)
Health is, beside of other services and commodities, e.g. education or social housing, a merit, quasi-public good. Since private provision of health services would presumptively not be sufficient in quality and quantity, one could argue there is a responsibility by the state to provide a sufficient amount of health services to its population. However, it is difficult to quantify the sufficient amount with public goods, in general. One required component of the healthcare provision is infrastructure, such as hospitals, operation theaters etc. and its related equipment, such as beds, imaging devices etc. To estimate the existing infrastructure in the European countries, without an on-the-ground evaluation, we use investment time series for tangible and intangible assets (Gross Fixed Capital Formation) reported to Eurostat and compute Capital Stock for each country, using the Perpetual Inventory Method (PIM) considering country specific depreciation rates and growth rates for each included asset. Based on the last computed capital stock in 2016 as benchmark, we evaluate the effect of the global financial crises in 2008. Furthermore, we run two future scenarios for EU28 in total and each country: (I) how much annual investment is needed, such that the capital stocks keep pace with annual GDP growth rates and (II) how much annual investment is needed, such that the 2016 capital stock per capita can be maintained in the future.
urn:nbn:de:bsz:291–ds-321239; hdl:20.500.11880/29744
Keywords: 300; Perpetual-Inventory-Method; investment time series; health infrastructure; Grundkapital; Europaïsche Union